Initial experience with single-port robot-assisted partial nephrectomy using the Low Anterior Access (LAA): perioperative outcomes and learning curve analysis in a Belgian SP-naive tertiary robotic referral center - Van Eecke, Henri; Grammens, Julien; De Kuyper, Peter; Verla, Wesley; Ameye, Filip; Crivellaro, Simone; Decaestecker, Karel (Frontiers in Surgery, 2026)
ObjectivesRobot-assisted partial nephrectomy (RAPN) has become a standard minimally invasive approach for localized renal tumors. The introduction of the single-port (SP) robotic system has enabled novel retroperitoneal techniques, such as the Low Anterior Access (LAA). This study presents the initial experience of SP RAPN using the LAA technique in a SP-naive Belgian tertiary robotic referral center.MethodsA retrospective database was created with prospectively collected data from patients who underwent SP RAPN via LAA between May 2024 and September 2025. All procedures were performed by a SP robot-naive surgeon with extensive multi-port transperitoneal robotic experience but no prior multi-port retroperitoneal exposure. Surgical and perioperative outcomes of SP RAPN, using the LAA technique, were the primary endpoint of this study. As a secondary endpoint we evaluated the learning curve of this procedure.ResultsForty patients underwent SP RAPN. Median tumor size was 26 mm, with a median RENAL score of 5. Median warm ischemia time was 17 min and median estimated blood loss was 50 ml. No intraoperative complications, conversions, or positive surgical margins occurred. Three minor postoperative complications (7.5%) were recorded, with no grade ≥III events. Median length of stay was one night and median postoperative pain scores (VAS) at 12 and 24 hours were 0. Operative time, warm ischemia time and estimated blood loss showed improvement over successive cases, reflecting increased procedural efficiency.ConclusionSP RAPN using the LAA technique is feasible and safe, even for a surgeon without prior SP or retroperitoneal experience. This first experience study demonstrated low morbidity, minimal postoperative pain, and early discharge. These findings support the adoption of SP RAPN via LAA as a viable option for minimally invasive nephron-sparing surgery, warranting validation in larger multicenter studies.